Project manager competency development framework (Project Management Institute, Inc., 2017)
Providing general context for the definition, assessment and development of project manager competency, this book outlines the key dimensions and identifies those competencies that are most likely to impact project manager performance. -- Edited summary from book.
Keywords: Project management -- Study and teaching.; elektronické knihy; electronic books